Pendugaan Cadangan Karbon Di Atas Permukaan Pada Hutan Rakyat Dengan Memanfaatkan Data Synthetic Aperture Radar Sentinel-1 (Studi Kasus Di Kabupaten Sukoharjo) - Bayanuddin, Athar Abdurrahman; , Dra. Alif Noor Anna, M.Si (2016)
The high amount of carbon dioxide in the atmosphere is one of the causes of global warming. Preserve carbon stocks is an effort to reduce carbon emissions, including in the community forest which need to be recorded. Remote Sensing Data of Sentinel-1 SAR (Synthetic Aperture Radar) was used to determine the above ground carbon stocks on community forest in Sukoharjo Regency. The objectives of this reasearh are: 1) analyze the relationship between the backscatter value of Sentinel-1 SAR dual polarization data and the value of carbon stock in community forest based on the above ground green biomass value; 2) to estimate above ground carbon stock of community forest in Sukoharjo Regency by utilizing the dual-polarization SAR Sentinel-1 data; and 3) to determine the total and the spatial distribution of above ground carbon stock on community forest in Sukoharjo Regency based on Sentinel-1 SAR data. The method was used in this study is a survey method using purposive sampling to complement remote sensing data related to biomass and above ground carbon stock in community forest using allometric equations based on the the extraction result of backscatter value of each polarization VV (Vertical-Vertical), VH (Vertical-Horizontal), and band ratio VV/VH. Statistical analysis was used to generate equation for estimating carbon stocks based on the SAR data and field data. Geographic Information System (GIS) was used to represent data spatially well as information of above ground carbon stock value and used spatial data analysis approach both quantitatively and qualitatively. The results showed that: 1) there is a significant and inversely relationship between the value of VV polarization backscatter (R = -0.438 (very low)) and VH polarization (R = -0.612 (Low)) on above graound carbon stock value. 2) How to Estimate Above ground carbon stock on community forest in Sukoharjo was obtained from Sentinel-1 SAR data using VH polarization with chosen simple linear regression equation (R2 = 0.375; RMSE = 101.1648) is Y = -61.499 -493.268 + X. The Total of above ground carbon stock in Sukoharjo Regency is 228,456.36 tons of 7738.287 hectares community forest and it has a spread spatial distribution pattern at random and clustered. The largest above ground biomass carbon stock is in the community forest of Bulu Sub-district is 49540.21 tons (1782.008 ha) and least in the Gatak Sub-district is 49.50 tons (1,357 ha).